PUSAT KEBUGARAN DAN RELAKSASI KHUSUS WANITA DI KOTA PONTIANAK DENGAN PENDEKATAN ARSITEKTUR POST-PANDEMIC - Retno Wulandari; Yudi Purnomo; Zairin Zain (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The COVID-19 pandemic has caused many public facilities to temporarily close, including fitness facility providers. Pontianak City is one of the major cities affected by the COVID-19 pandemic. The temporary closure of fitness facilities in Pontianak City resulted in the unavailability of fitness facilities for the community. The COVID-19 pandemic has evoked a trend of healthy living, thus providing opportunities for the rise of fitness and health facilities. Generally, fitness and relaxation facilities have a mix of male and female activities. The combination of activities between the two sexes causes discomfort for women. The design is carried out with the stages of introduction, definition, preparation, analysis, synthesis, evaluation and reevaluation. The result of the design is a building that accommodates women in Pontianak City in carrying out physical and psychological fitness activities with emphasis on the comfort and health aspects of space. The aspect of space comfort in the building is realized by placing the space zone and choosing the type of circulation to create an atmosphere of private space. The design of the Women's Special Fitness and Relaxation Center in Pontianak City uses a Post-Pandemic Architecture approach aimed at creating a pandemic response room design. Efforts to create healthy spaces are carried out by using natural ventilation (openings and gardens) and artificial ventilation (bipolar purification technology). The building uses a smart technology system on touch areas such as doorknobs as well as material selection that considers the length of life of the virus on the surface area.